Laboratory measure of cheating predicts school misconduct - Alain Cohn; Michel André Maréchal (University of Zurich, Department of Economics, 2016)
We conducted an experiment with middle and high school students to test the external validity of a common laboratory measure of cheating. Subjects performed several coin tosses and earned money depending on the outcomes they reported. Because the coin tosses were not monitored, subjects faced a financial incentive to misreport their outcomes without having to worry about getting caught. We linked the responses from the lab experiment with three measures of school misconduct (i.e., disruptiveness in class, failure to complete homework, and absenteeism). The findings show that cheating in the lab significantly predicts misbehavior in school, suggesting that the experimental measure of cheating generalizes qualitatively to naturally occurring environments.
Keywords: C93; K42; 330; Cheating; Honesty; Experiment; External Validity; School Misbehavior